Characteristic and antioxidant activity of Cladophora glomerata ethanolic extract as affected by prior chlorophyll removal and drying methods - Suthasinee Yarnpakdee; Theeraphol Senphan; Sutee Wangtueai; Chalalai Jaisan; Sitthipong Nalinanon (Journal of Food Processing and Preservation, 2021)
Impact of prior chlorophyll removal (PCR) and drying methods (freeze- and oven-drying) on characteristics and antioxidant activities of the ethanolic extracts (EEs) from Cladophora (C.) glomerata, freshwater macroalgae, were investigated. The extraction yields were found in the range of 7.18%–13.15% with total phenolic (TPC) and total chlorophyll (TCC) contents of 19.40–25.69 mg GAE/g dry extract and 3.58–7.94 mg/g dry extract, respectively. Yield, TPC and TCC decreased when dechlorophyllization was implemented before extraction, regardless of drying method (p ≤ .05). Increase in L* value with coincidental decrease in ΔE* value was observed in the EE with PCR. Freeze-dried EE with PCR (FEE-PCR) showed greater antioxidant efficiencies (both in vitro and oxidation model systems) than that oven-dried EE with PCR (p ≤ .05). Liquid chromatography/mass spectrometry (LC/MS) analysis indicated that quercetin-3-O-glucoside was the most abundant phenolic compounds identified in the FEE-PCR. Therefore, freeze drying in combination with PCR was effective preparation method to maximize antioxidant activity and improve color of EE. Practical applications Lipid oxidation is one of important reactions affected on the deterioration of food quality and safety. Many antioxidants have been widely used to retard lipid oxidation. Due to their health hazard of synthetic antioxidants, the search for safer ingredients with potent antioxidant activity resources is attracted interest. Phenolic compounds, the bioactive substances distributed in aquatic plants, have been known as antioxidant with health benefit. However, chlorophyll associated algal extract influenced on color and bioactivity of phenolic compound, which limits its utility. Moreover, drying technologies also have an impact on a stability of active components in algal sample. To maximize the utility of alga, the appropriate pretreatments by chlorophyll removal along with effective drying method could be a better choice for preservation of bioactive compounds. As a consequence, a wider application can be achieved. The corresponding extracts could therefore be used as an alternative natural antioxidant for food applications, instead of synthetics in a future.
Keywords: Seaweed-derived Bioactive Compounds; Algal biology and biofuel production; Phytochemicals and Antioxidant Activities